A praat-based stuttering analysis of the main character in the king’s speech movie: a neuropsycholinguistic study - Yonnie Kharismadewi; Ike Revita; Rina Marnita AS (Politeknik Negeri Bali, 2023)
Stuttering is a speech disorder characterized by involuntary repetitions or prolongations of words or syllables, or by involuntary interruptions in the flow of speech, known as blocks. Stuttering can happen due to genetics and environmental factors or psychogenic. This research aims to identify the types of stuttering that occur and to explain the factors that contribute to stuttering and the effect on the main character's speech fluency in the movie